Ethnobotany of spring waters based on species toponymy on the east slope of Mount Ijen, Banyuwangi District, Indonesia - RIYAN RIYADLUN NAJIH; JATI BATORO; LUCHMAN HAKIM (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Najih RR, Batoro J, Hakim L. 2023. Ethnobotany of spring waters based on species toponymy on the east slope of Mount Ijen, Banyuwangi District, Indonesia. Biodiversitas 24: 3860-3871. Some spring waters in Banyuwangi are unique in terms of toponymy (place name), where local communities give names to springs based on plant species around the springs. This research aimed to (i) understand the names of the plants used as the design names for the springs, (ii) understand the plants in the offerings of the springs and (iii) explain the use of plants around the springs on the East Ijen Slopes, Banyuwangi District, Indonesia. A field study was conducted on the slopes of Mount Ijen. Research data were obtained from 50 informants through semi-structured interviews. This study used descriptive analysis and Relative Frequency of Citations (RFC). There were five toponymy species of springs, namely Pangium edule Reinw, Planchonia valida (Blume) Blume, Terminalia sp., Ganophyllum falcatum Blume, and Garcinia tetranda Pierre. Offerings dishes of springs were Pecel Pitik, Tajin Suro, Tajin Jenang Limo, and Tumpeng Serakat. There are 43 species of plants around the springs within 21 families. Plants with the highest RFC values were Gigantochloa apus (Schult. f.) Kurz ex Munro (0.62), followed by Ficus benjamina L. (0.4) and S. mahagoni (L.) Jacq (0.32). In terms of utilization, the toponymy species did not have the highest RFC value. Species with low RFC values have a greater possibility of extinction than other species.